2016
DOI: 10.1021/acs.joc.6b00123
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Friedel–Crafts Alkylation Reactions of 3-Substituted Indoles with Electron-Deficient Alkenes

Abstract: Highly enantioselective Friedel-Crafts C2-alkylation reactions of 3-substituted indoles with α,β-unsaturated esters and nitroalkenes were developed using chiral Lewis acids as catalysts, which afforded chiral indole derivatives bearing C2-benzylic stereogenic centers in good to excellent yields (up to 99%) and enantioselectivities (up to 96% ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…This reaction was performed with α,β-unsaturated esters 686 and was sensitive only to bulky substituents on the indole ring. 258 …”
Section: Bis(oxazoline) Ligandsmentioning
confidence: 99%
“…This reaction was performed with α,β-unsaturated esters 686 and was sensitive only to bulky substituents on the indole ring. 258 …”
Section: Bis(oxazoline) Ligandsmentioning
confidence: 99%
“…Scheme 66. Friedel-Crafts C2-alkylation of 3-substituted indoles with nitroalkenes in the presence of a bisoxazoline ligand [97].…”
Section: Michael Additionsmentioning
confidence: 99%
“…On the other hand, Frie-del-Crafts reaction occurring at the less reactive C2 position of indoles to deliver biologically potential chiral indoles bearing C2benzylic stereocenters remain rare. To fill this gap, Jia et al reported in 2016 an enantioselective Friedel-Crafts C2-alkylation reaction of 3-substituted indoles 197 with nitroalkenes 26 catalyzed by a chiral zinc complex derived from bisoxazoline ligand 198 [97]. As illustrated in Scheme 66, the process furnished chiral indole derivatives 199 bearing C2-benzylic stereogenic centers in Scheme 69.…”
Section: Friedel-crafts Reactionsmentioning
confidence: 99%
“…The reactions proceeded smoothly to deliver the desired C2-alkylated indoles in excellent enantioselectivities in the presence of chiral Lewis acid catalysts. 15 In the case of α,β-unsaturated ester substrates, it was found that Cu(OTf) 2 /(S)-i Pr-bisoxazoline L3 was the best catalyst, affording excellent yields and enantioselectivities (Scheme 8). Whereas, for the reaction with nitroalkenes as alkylating agents, the complex of Zn(OTf) 2 with Du's bisoxazoline L4 turned out to be an efficient catalyst resulting in the desired products in excellent yields and enantioselectivities (Scheme 9).…”
Section: Account Syn Lettmentioning
confidence: 99%